Desafios da Igreja do século XXI - Vélez Caro, Olga Consuelo (Revista eclesiástica brasileira, 2005)
By analysing the Vaticano II’s contexto and the changes it has brought to ecclesiastic life, the present article contemplates some challenges that have come along with this new millennium, and how the current Church should face them. For instance, the commitment with the poor and excluded ones of the Continent, the rescue of the human being as a whole, the return to sacredness, the passage from the mega-reports to articulation through networks, the valorization of cultures, the awakening of ecological consciousness, and the reflection on gender. These are not all the issues; however, some of them are considered urgent and necessary in the Latin-American context to guarantee that the Church be significant and pertinent for today’s men and women.